Electrode catalyst layer, membrane electrode assembly, and fuel cell

The electrocatalyst layer, featuring oxygen-rich carbon fibers and silane coupling agent treatment, addresses the issue of reduced proton conductivity in fuel cells, resulting in enhanced output characteristics and power generation performance.

JP2025047254APending Publication Date: 2025-04-03TOPPAN HOLDINGS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023155643
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing electrocatalyst layers in fuel cells experience reduced proton conductivity due to increased voids, which compromises the output characteristics despite improved gas permeability.

Method used

An electrocatalyst layer comprising carbon fibers with a core-shell structure, where the shell portion has a higher oxygen concentration, is combined with catalyst particles and ionomers. The surface of the carbon fibers is treated with a silane coupling agent to enhance ionomer adhesion and proton conductivity.

Benefits of technology

The proposed electrocatalyst layer achieves excellent output characteristics by maintaining high proton conductivity while enhancing gas permeability, leading to improved power generation performance in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047254000001_ABST
    Figure 2025047254000001_ABST
Patent Text Reader

Abstract

To provide an electrode catalyst layer etc. that have excellent output characteristics during power generation.SOLUTION: An electrode catalyst layer includes carbon fibers, catalyst particles, and an ionomer. The carbon fibers 2 have a core portion 2a and a shell portion 2b having a higher concentration of oxygen atoms than the core portion 2a. The ratio of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fibers 2 measured by XPS is 1% or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode catalyst layer, a membrane electrode assembly, and a fuel cell. [Background technology]

[0002] A known solid polymer fuel cell is one that includes an electrolyte layer formed from an ion exchange resin, a fuel-side electrode (anode) to which fuel is supplied, and an oxygen-side electrode (cathode) to which oxygen is supplied.

[0003] In such a fuel cell, fuel is supplied to the anode and air is supplied to the cathode, which generates an electromotive force and generates electricity.

[0004] As a cathode catalyst, for example, a platinum-supported carbon catalyst in which platinum is supported on carbon has been proposed, but since expensive platinum is used, it is desired to obtain high output with a smaller amount of platinum. In response to this problem, attempts have been made to improve the activity of the catalyst by using an alloy of platinum with cobalt or the like. However, the elements used in the alloy are often more easily eluted than platinum, and there are problems with durability. On the other hand, attempts have been made to increase output by focusing on optimizing the environment on the platinum surface and the structure of the catalyst layer.

[0005] In optimizing the environment on the platinum surface, it has been reported that by encapsulating metal particles with a porous inorganic material and impregnating them with an ionic liquid, it is possible to improve oxygen reduction activity and inhibit the elution of metal particles (Patent Document 1).

[0006] Regarding the structure of the electrode catalyst layer, it has been reported that an electrode catalyst layer formed by mixing fibrous carbon improves gas permeability and power generation characteristics (Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. WO2023 / 277148 [Patent Document 2] Patent No. 3608053 Summary of the Invention [Problem to be solved by the invention]

[0008] The electrode catalyst layer containing fibrous carbon had increased pores in the electrode catalyst layer compared to an electrode catalyst layer without the fibrous carbon, and as a result, gas permeability was improved, but proton conductivity was reduced, and the output obtained could not be said to have been sufficiently improved. The decrease in proton conductivity is believed to be due to the increase in pores in the electrode catalyst layer, which reduced the amount of ionomer per unit volume of the electrode catalyst layer and reduced the number of proton conduction paths.

[0009] The present invention has been made in view of the above-mentioned points, and has an object to provide an electrode catalyst layer, a membrane electrode assembly for a fuel cell, and a fuel cell that are excellent in output characteristics during power generation. [Means for solving the problem]

[0010] [1] An electrode catalyst layer comprising carbon fibers, catalyst particles, and an ionomer, The carbon fiber has a core portion and a shell portion having a higher concentration of oxygen atoms than the core portion, An electrode catalyst layer, in which the ratio of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fiber as measured by XPS is 1% or more.

[0011] [2] The electrode catalyst layer according to [1], wherein the surface of the carbon fiber is covered with the ionomer.

[0012] [3] The electrode catalyst layer according to [1] or [2], wherein the surface of the carbon fiber is treated with a silane coupling agent.

[0013] [4] The electrode catalyst layer according to [3], wherein the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane.

[0014] [5] A membrane / electrode assembly comprising a polymer electrolyte membrane and the electrode catalyst layer according to any one of [1] to [4] provided on at least one surface of the polymer electrolyte membrane.

[0015] [6] A solid polymer fuel cell comprising the membrane electrode assembly described in [5]. Effect of the Invention

[0016] According to the present invention, there are provided an electrode catalyst layer, a membrane electrode assembly for a fuel cell, and a fuel cell, which have excellent output characteristics during power generation. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electrode catalyst layer 10 according to one embodiment. [Diagram 2] FIG. 2 is an enlarged schematic cross-sectional view of the carbon fiber 2 in FIG. [Diagram 3] FIG. 3 is an enlarged schematic cross-sectional view of a membrane electrode assembly 1 according to an embodiment. [Figure 4] FIG. 4 is an exploded perspective view of a fuel cell 3 according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the present invention is not limited to the embodiment described below, and modifications such as design changes can be made based on the knowledge of those skilled in the art, and such modified embodiments are also included in the scope of the present invention. Also, the drawings are appropriately exaggerated to facilitate understanding.

[0019] (Configuration of electrode catalyst layer 10) An electrode catalyst layer 10 according to an embodiment of the present invention includes carbon fibers 2, catalyst particles 6, and an ionomer 8, as shown in FIG.

[0020] (Carbon Fiber 2) 2, the carbon fiber 2 has a core portion 2a and a shell portion 2b having a higher concentration of oxygen atoms than the core portion 2a. The core portion 2a is a portion consisting essentially of carbon atoms, and the shell portion 2b is a portion containing carbon atoms and oxygen atoms.

[0021] The high oxygen concentration in the shell portion 2b means that the shell portion 2b has a carbon atom bonded to a hydroxyl group (C-OH) and / or a carbonyl group (>C=O). When the shell portion 2b has a higher oxygen concentration than the core portion 2a, the hydrophilicity of the carbon fiber 2 increases.

[0022] The ratio of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fiber measured by XPS is 1% or more, and from the viewpoint of ensuring the electrical conductivity of the carbon fiber, this ratio may be 10% or less.

[0023] (Plasma treatment) Such carbon fiber 2 can be obtained by subjecting carbon fiber to plasma treatment. Plasma treatment is a mild treatment that can selectively introduce oxygen atoms onto the surface of the carbon fiber, and causes little damage to the inside of the carbon fiber. Therefore, it is easy to suppress wear of the carbon fiber during durability testing of the fuel cell.

[0024] The plasma treatment is not particularly limited, but may be, for example, a known low-temperature plasma treatment. The low-temperature plasma treatment is a method in which a high voltage is applied while a specific gas is being supplied, and the surface of the carbon fiber is treated with the generated plasma.

[0025] The predetermined gas is not particularly limited, but may be nitrogen gas, oxygen gas, or the like. Oxygen gas is particularly preferred. Oxygen gas plasma treatment can more actively introduce oxygen atoms to the surface. The treatment device is not particularly limited, and a known internal electrode type or external electrode type may be used, but the external electrode type is preferred in terms of no contamination of the electrodes. Treatment conditions such as treatment pressure, power frequency, and treatment output are not particularly limited, and may be selected as appropriate depending on the purpose.

[0026] The carbon fiber to be treated, in other words, the material constituting the core portion 2a of the carbon fiber 2, is not particularly limited, but vapor grown carbon fiber (VGCF), single-walled carbon nanotubes, and multi-walled carbon nanotubes are preferred, and VGCF is more preferred. VGCF has a larger fiber diameter and fiber length than carbon nanotubes, and the use of carbon fiber with a shell portion formed on the surface of VGCF can favorably increase gas permeability.

[0027] The carbon fibers may have an average fiber diameter of 100 to 200 nm and an average fiber length of 3 to 5 μm. The fiber diameter of the carbon fibers can be obtained, for example, by measuring the diameter of the carbon fibers exposed on the cross section of the electrode catalyst layer when the cross section is observed using a scanning electron microscope (SEM). When the fibrous material 15 is cut obliquely, the shape of the exposed cross section may be elliptical. In that case, the fiber diameter of the fibrous material 15 can be obtained by measuring the diameter of a perfect circle fitted along the minor axis. The average fiber diameter can be obtained by measuring the fiber diameters of multiple, for example 20, points of the fibrous material 15 and calculating the arithmetic average.

[0028] The average fiber length of carbon fibers refers to the arithmetic average value of the fiber lengths obtained by measuring at least 10 carbon fibers. The average fiber length of the coated fibers in the electrode catalyst layer can be obtained by performing particle size distribution measurement using a solution in which the electrode catalyst layer is dissolved in a solvent. Specifically, the correlation between the average fiber length obtained by an electron microscope and the peak position in the particle size distribution measurement is grasped in advance, and the average fiber length of the carbon fibers in the electrode catalyst layer is obtained based on this correlation and the peak position obtained by the particle size distribution measurement.

[0029] (Silane coupling agent treatment) The surface of the carbon fiber 2 may be further treated with a silane coupling agent. Although there is no particular limitation on the silane coupling agent, the silane coupling agent is preferably one having a functional group including an amino group.

[0030] In particular, the silane coupling agent is preferably one represented by formula (1). Here, R is an aminoalkyl group such as a 3-aminopropyl group or a 3-(2-aminoethylamino)propyl group, and the number of carbon atoms of the alkyl group may be 1 to 10. Among them, the R group is preferably a 3-aminopropyl group or a 3-(2-aminoethylamino)propyl group. Furthermore, R' in OR', which is an alkoxy group, is not particularly limited as long as it is an alkyl group (which may have a carbon number of 1 to 10), but a methyl group or an ethyl group is preferably used. In particular, it is preferable from the viewpoint of reactivity that the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane.

[0031] [ka]

[0032] By further treating the surface of the shell portion 2b of the carbon fiber 2 with a silane coupling agent, it is possible to impart hydrophilic functional groups R to the surface of the shell portion 2b and increase the amount of ionomer attached.

[0033] By treating the carbon fiber with a silane coupling agent after forming a shell portion with a high oxygen concentration by plasma treatment or the like in advance, reactions such as dehydration condensation between hydroxyl groups and / or carbonyl groups and the alkoxy groups of the silane coupling agent can occur more easily. This allows the surface treatment with the silane coupling agent to be carried out more smoothly, and makes it easier to modify the surface of the carbon fiber with functional groups having aminoalkyl groups such as aminopropyl groups.

[0034] The aminoalkyl group has high reactivity with the ionomer and contributes to the formation of a proton conductive path by the ionomer.

[0035] (Ionomer coating of carbon fibers) As shown in FIG. 2, the surface of the carbon fiber 2 can be coated with an ionomer 8 .

[0036] There is no limitation on the amount of ionomer coating on the carbon fibers, but for example, when a cross section of the electrode catalyst layer is cut out, and the carbon fiber portion is measured at 10 points by TEM-EDS, and the average value of the ratio (F / C) of the number of F atoms to the number of C atoms in the carbon fiber portion is calculated, the ratio is preferably 0.001 or more, may be 0.002 or more, may be 0.003 or more, or may be 0.004 or more. The average value of the ratio (F / C) may be 0.1 or less, may be 0.05 or less, may be 0.02 or less, or may be 0.01 or less.

[0037] (Ionomer (Polyelectrolyte) 8) Although there is no particular limitation on the ionomer (polymer electrolyte) 8, it is preferable that the ionomer is an ionomer having proton conductivity. Examples of the ionomer include a fluorine-based polymer electrolyte and a hydrocarbon-based polymer electrolyte. As the fluorine-based polymer electrolyte, a polymer electrolyte having a tetrafluoroethylene skeleton can be used. An example of the polymer electrolyte having a tetrafluoroethylene skeleton is Nafion (registered trademark) manufactured by DuPont. As the hydrocarbon-based polymer electrolyte, for example, sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene can be used.

[0038] (Catalyst particles 6) As shown in FIG. 1, the catalyst particle 6 has a conductive support 6a and a plurality of metal particles 6b supported on the conductive support 6a.

[0039] (Conductive carrier 6a) The conductive support 6a is not particularly limited in terms of material, so long as it is particles of a conductive material. The conductive support is preferably carbon particles. The conductive support may be spherical particles. In particular, it is preferable that the conductive support is carbon particles having a peak intensity ratio (G / D ratio) of G band to D band by Raman spectroscopy of 1.2 to 2.2. Also, it is preferable that the conductive support is carbon particles having the above-mentioned peak intensity ratio (G / D ratio) of 1.6 or more. In this embodiment, the wavelength of the laser light used in Raman spectroscopy is 532 nm. In this embodiment, the G band by Raman spectroscopy is a wavelength of 1580 cm -1 The Raman peak located around 1360 cm is called the D band. -1 This means a Raman peak located near the center of the conductive support. The particle size of the conductive support may be about 10 nm or more and 1000 nm or less, and may be about 10 nm or more and 100 nm or less. The particle size of the conductive support is a volume average diameter measured by a laser diffraction / scattering method.

[0040] (metal particle 6b) The metal particles supported on the conductive support preferably contain one or more of Pt, Rh, Pd, Au, and Ir. For example, Pt alone, alloy particles of Pt and Co, or core-shell particles in which Pt particles are coated on a Pd core may be used.

[0041] In addition, the metal particles are preferably Pt particles having a crystallite size (1,1,1) of 8 nm or less, more preferably 5 nm or less, as determined by the XRD method. Here, the (1,1,1) indicates Miller indices. If the Pt particles have a crystallite size (1,1,1) of 8 nm or less, the catalytic activity is high and a high voltage can be obtained. Furthermore, if the Pt particles have a crystallite size (1,1,1) of 3 nm or more and 4 nm or less, high catalytic activity can be reliably obtained. The average particle size of the metal particles may be 0.5 nm or more and 20 nm or less, and may be 1 nm or more and 5 nm or less. The particle size of the metal particles is the average diameter determined by analysis of a TEM image (for example, JIS H7804:2005).

[0042] The ratio of the metal in the catalyst particles can be 10 to 50 mass %.

[0043] (Composition of electrode catalyst layer) The composition of the electrode catalyst layer is not particularly limited, but the mass of the conductive support in the catalyst particles can be 1, the mass of the ionomer (polymer electrolyte) (solid content) can be 0.5 to 1.2, and the mass of the carbon fiber can be 0.01 to 0.5.

[0044] The electrode catalyst layer according to this embodiment may be a cathode electrode catalyst layer or an anode electrode catalyst layer.

[0045] (Membrane Electrode Stack) Next, the configuration of the membrane electrode assembly 1 will be described with reference to Fig. 3. The membrane electrode assembly 1 includes a polymer electrolyte membrane 11, and an anode electrode catalyst layer 10A and a cathode electrode catalyst layer 10C bonded to the front and back surfaces of the polymer electrolyte membrane 11, respectively.

[0046] The cathode electrode catalyst layer 10C constitutes an oxygen electrode, and the anode electrode catalyst layer 10A constitutes a fuel electrode. The constituent material of the polymer electrolyte membrane 11 can be the same as that explained for the ionomer above.

[0047] In the membrane electrode assembly 1 according to the present embodiment, both the cathode electrode catalyst layer 10C and the anode electrode catalyst layer 10A may be the above-mentioned electrode catalyst layer 10, or either one of them may be the above-mentioned electrode catalyst layer 10. It is preferable that at least the cathode electrode catalyst layer 10C of the membrane electrode assembly 1 is the above-mentioned electrode catalyst layer 10.

[0048] (Polymer electrolyte fuel cell 3) Next, a specific configuration example of a polymer electrolyte fuel cell 3 including the membrane electrode assembly 1 according to this embodiment will be described with reference to Fig. 4. Fig. 4 is an exploded perspective view showing a configuration example of a polymer electrolyte fuel cell 3 equipped with the membrane electrode assembly 1. Note that Fig. 4 shows an example of the configuration of a single cell, and the polymer electrolyte fuel cell 3 is not limited to this configuration and may have a configuration in which a plurality of single cells are stacked.

[0049] As shown in FIG. 4, the polymer electrolyte fuel cell 3 includes a membrane electrode assembly 1, a gas diffusion layer 22C, and a gas diffusion layer 22A. The gas diffusion layer 22C is disposed opposite the cathode electrode catalyst layer 10C on the oxygen electrode side of the membrane electrode assembly 1. The gas diffusion layer 22A is disposed opposite the anode electrode catalyst layer 10A on the fuel electrode side of the membrane electrode assembly 1. The cathode electrode catalyst layer 10C and the gas diffusion layer 22C constitute an oxygen electrode 2C, and the anode electrode catalyst layer 10A and the gas diffusion layer 22A constitute a fuel electrode 2A. In order to prevent gas leakage from the outer periphery of the polymer electrolyte membrane 11 to which the electrode catalyst layer is not joined, a gasket 16C on the oxygen electrode side and a gasket 16A on the fuel electrode side are disposed.

[0050] Furthermore, the solid polymer electrolyte fuel cell 3 includes a separator 23C arranged opposite the oxygen electrode 2C and a separator 23A arranged opposite the fuel electrode 2A. The separator 23C includes a gas flow path 24C for flowing a reactant gas formed on a surface facing the gas diffusion layer 22C, and a cooling water flow path 25C for flowing cooling water formed on a surface opposite to the surface on which the gas flow path 24C is formed. The separator 23A has a similar configuration to the separator 23C, and includes a gas flow path 24A formed on a surface facing the gas diffusion layer 22A, and a cooling water flow path 25A formed on a surface opposite to the surface on which the gas flow path 24A is formed. The separators 23C and 23A are made of a material that is conductive and gas impermeable.

[0051] In the solid polymer fuel cell 3, an oxidant such as air or oxygen is supplied to the oxygen electrode 2C through the gas flow path 24C of the separator 23C, and a fuel gas containing hydrogen or an organic fuel is supplied to the fuel electrode 2A through the gas flow path 24A of the separator 23A, thereby generating electricity.

[0052] By employing the membrane electrode assembly 1 according to this embodiment, it is possible to obtain sufficient gas diffusivity and proton conductivity, and to exhibit high power generation performance over a long period of time.

[0053] That is, according to this embodiment, it is possible to provide an electrode catalyst layer 10, a membrane electrode assembly 1, and a polymer electrolyte fuel cell 3 that have sufficient proton conductivity during operation of the polymer electrolyte fuel cell and can exhibit high power generation performance. Therefore, the present invention can be suitably used in stationary cogeneration systems and fuel cell vehicles that use polymer electrolyte fuel cells, and further in hydrogen production electrolysis systems that use membrane electrode assemblies, and has great industrial utility.

[0054] (Action and effect) According to this embodiment, the following effects are obtained. (1) The electrode catalyst layer according to this embodiment contains carbon fibers, catalyst particles, and an ionomer. The carbon fibers 2 have a shell portion 2b that has a higher oxygen atom concentration than a core portion 2a.

[0055] According to such a configuration, the oxygen concentration on the surface of the carbon fiber 2 is high, that is, the surface of the carbon fiber 2 is hydrophilized by a functional group containing an oxygen atom, so that the ionomer 8 is easily attached to the surface of the carbon fiber 2.

[0056] By attaching the ionomer 8 to the surface of the carbon fiber 2, in addition to improving the porosity of the electrode catalyst layer by the carbon fiber 2, a proton conductive path can be constructed on the surface of the carbon fiber, making it possible to provide an electrode catalyst layer for a fuel cell, a membrane electrode assembly 1, and a fuel cell that are excellent in both gas permeability and proton conductivity. Note that, in the case of carbon fiber that has not been subjected to a plasma hydrophilization treatment, oxygen was not observed on the surface by XPS.

[0057] (2) When the surface of the carbon fiber is further treated with a silane coupling agent, the hydrophilicity of the surface is further increased by the silane coupling agent treatment, and the amount of ionomer attached to the surface of the carbon fiber can be further increased. This further increases the proton conductivity and improves the power generation characteristics. Furthermore, even when untreated carbon fiber that has not been subjected to plasma hydrophilization treatment is treated with silane coupling agent, there is almost no reaction with the silane coupling agent, and the amount of ionomer attached is only slightly increased compared to the untreated carbon fiber.

[0058] (3) When the silane coupling agent according to this embodiment is an alkoxysilane having a functional group having the above-mentioned aminoalkyl group, the surface of the carbon fiber can be modified with the aminoalkyl group, and these functional groups can form ionic bonds with the sulfonic acid groups of the ionomer, etc., and therefore the amount of ionomer attached can be increased.

[0059] The electrode catalyst layer and membrane electrode assembly for a fuel cell according to this embodiment will be described below with reference to specific examples and comparative examples, but this embodiment is not limited to the following examples and comparative examples. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0061] Example 1 A cathode catalyst ink was prepared by adding plasma-treated VGCF (carbon fiber), Pt-supported carbon (catalyst particles: Pt / C=70 / 30 wt / wt), and Nafion dispersion (ionomer: Sigma-Aldrich) to a mixed solution (7:2:1) of water, NPA (normal propyl alcohol), and ethanol, and dispersing the mixture in a ball mill. The I (ionomer) / C (carbon support) ratio was 0.8, the carbon fiber / C (carbon support) ratio was 0.1, and the solid content was 12 wt%. The prepared cathode catalyst ink was applied to a Nafion membrane with a Pt basis weight of 0.4 mg / cm. 2 The coating was then dried at 80° C. for 5 minutes to obtain a cathode-side catalyst layer. Note that oxygen gas was used for the plasma treatment.

[0062] Next, VGCF, Pt-supported carbon (Pt / C=30 / 70 wt / wt), and Nafion dispersion (Sigma-Aldrich) were added to a mixed solution (7:2:1) of water, NPA (normal propyl alcohol), and ethanol, and dispersed using a ball mill to prepare an anode catalyst ink. The I / C ratio was 1.0, and the carbon fiber / C (carrier carbon) ratio was 0.1. The prepared anode catalyst ink was applied to the Nafion membrane on the side opposite to the cathode catalyst layer, with a Pt weight of 0.1 mg / cm. 2 Subsequently, the coating was dried at 80° C. for 5 minutes, and an anode-side catalyst layer was placed thereon to obtain a membrane electrode assembly.

[0063] Example 2 The plasma-treated VGCF was added to water in the same manner as in Example 1, followed by the addition of a mixed solution of 3-aminopropyltriethoxysilane and ethanol. Sodium hydroxide was added and the mixture was stirred for 2 hours, after which the VGCF was separated using a centrifuge and dried at 80°C for 6 hours to obtain plasma-treated VGCF treated with a silane coupling agent.

[0064] Next, in the same manner as in Example 1, a cathode catalyst ink was prepared using the plasma-treated VGCF, and a membrane electrode assembly was fabricated.

[0065] Example 3 The plasma-treated VGCF was added to water in the same manner as in Example 1, followed by the addition of a mixed solution of 3-(2-aminoethylamino)propyltriethoxysilane and ethanol. Sodium hydroxide was added and the mixture was stirred for 2 hours, after which the VGCF was separated in a centrifuge and dried at 80°C for 6 hours to obtain plasma-treated VGCF treated with a silane coupling agent.

[0066] Next, in the same manner as in Example 1, a cathode catalyst ink was prepared using the plasma-treated VGCF, and a membrane electrode assembly was fabricated.

[0067] Comparative Example 1 A membrane / electrode assembly was produced in the same manner as in Example 1, except that in the preparation of the cathode catalyst ink, untreated VGCF was used instead of the plasma-treated VGCF.

[0068] Comparative Example 2 Untreated VGCF was added to water, followed by the addition of a mixed solution of 3-aminopropyltriethoxysilane and ethanol. Sodium hydroxide was added and stirred for 2 hours, after which the VGCF was separated using a centrifuge and dried at 80°C for 6 hours to obtain VGCF treated with a silane coupling agent. Then, similar to Example 1, a cathode catalyst ink was prepared using the treated VGCF, and a membrane electrode assembly was produced.

[0069] (The ratio of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fiber measured by XPS) The X-ray source was a monochromated AlKα ray (1486.6 eV) operated at 225 W, and the ratio X of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fiber after plasma treatment was measured from the C1s and O1s spectra. Note that the silane coupling treatment does not substantially affect the number of oxygen atoms.

[0070] (Ionomer adhesion amount) A cross section of the produced membrane electrode assembly was cut out, and the carbon fiber portion was measured at 10 points by TEM-EDS to determine the average value of the number of F atoms / number of C atoms in the carbon fiber portion.

[0071] (IV measurement method) A gas diffusion layer and a gas seal were laminated on both sides of the obtained membrane electrode assembly, and a Japan Automobile Research Institute (JARI) standard cell (electrode area 5 × 5 cm) was used. 2 ) and the cell evaluation and analysis protocol of the New Energy and Industrial Technology Development Organization (NEDO) was followed. The current density was shifted from low to high while being held at the measurement current density for 5 minutes. The measurement current densities were 0, 0.025, 0.050, 0.075, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.5, 1.6, 1.8, and 2.0 A / cm. 2 It was decided.

[0072] The evaluation results are shown in Table 1.

[0073] [Table 1]

[0074] Table 1 shows the IV measurement results of 2.0A / cm 2 When the voltage was lower than that of Comparative Example 1, it was marked with an "X". When the voltage was higher than Comparative Example 1 by less than 10 mV, it was marked with a "△". When the voltage was higher than Comparative Example 1 by 10 mV or more but less than 20 mV, it was marked with an "O". When the voltage was higher than Comparative Example 1 by 20 mV or more, it was marked with an "◎".

[0075] In comparison with Comparative Example 1, the carbon fiber of Example 1 had a shell portion with a high oxygen concentration due to the plasma treatment, and the F atom / C atom ratio in the carbon fiber portion in the electrode catalyst layer was increased, and it was confirmed that the amount of ionomer attached to the carbon fiber was increased, and the voltage during power generation was also improved.

[0076] In Example 2, in which the plasma-treated carbon fiber was further subjected to a silane coupling treatment, the amount of inomer attached to the electrode catalyst layer was increased, and the voltage during power generation was also improved.

[0077] In the case of the silane coupling agent of Example 3, the amount of ionomer attached to the electrode catalyst layer was the largest, and the voltage during power generation was sufficiently improved compared to Comparative Example 1, but was not improved as much as in Example 2. If the amount of ionomer attached increases too much, it is considered that the void distribution in the electrode catalyst layer changes, and gas diffusivity may decrease slightly.

[0078] On the other hand, in the VGCF of Comparative Example 2, which was subjected to a silane coupling treatment without a plasma treatment, the amount of ionomer attached hardly increased, and the voltage also did not change much.

[0079] (Confirmation of hydrophilicity of carbon fiber) The carbon fiber obtained in Example 1 and the untreated carbon fiber of Comparative Example 1 were ultrasonically dispersed in water, and the settling state of the carbon fiber lumps after 24 hours was evaluated and confirmed. The distance from the water surface to the settled carbon fiber lumps was about half that of the untreated carbon fiber. When hydrophilicity is improved, the carbon fibers are less likely to aggregate in water, and the lumps are less likely to settle. [Industrial Applicability]

[0080] The fuel cell electrode material according to the present invention is used as an electrode for the power sources of various portable electronic devices, automobiles, and household electrical appliances. [Explanation of symbols]

[0081] Reference Signs List 1: membrane electrode assembly, 2: carbon fiber, 2a: core portion, 2b: shell portion, 3: solid polymer fuel cell, 11: polymer electrolyte membrane, 6: catalyst particle, 8: ionomer (polymer electrolyte), 10: electrode catalyst layer, 10A: anode electrode catalyst layer (electrode catalyst layer), 10C: cathode electrode catalyst layer (electrode catalyst layer).

Claims

1. An electrode catalyst layer comprising carbon fibers, catalyst particles, and an ionomer, The carbon fiber has a core portion and a shell portion having a higher concentration of oxygen atoms than the core portion, an electrode catalyst layer, in which the ratio of the number of oxygen atoms to the total number of carbon atoms and oxygen atoms on the surface of the carbon fiber as measured by XPS is 1% or more.

2. The electrode catalyst layer according to claim 1 , wherein a surface of the carbon fiber is coated with the ionomer.

3. 3. The electrode catalyst layer according to claim 1, wherein the surface of the carbon fiber is treated with a silane coupling agent.

4. 4. The electrode catalyst layer according to claim 3, wherein the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane.

5. A membrane electrode assembly comprising: a polymer electrolyte membrane; and the electrode catalyst layer according to claim 1 or 2 provided on at least one surface of the polymer electrolyte membrane.

6. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 5 .

Citation Information

Patent Citations

  • Cell catalyst composition, gas diffusion layer, and fuel cell provided with these

    JP3608053B2

  • Ionic liquid-impregnated catalyst particles, membrane electrode assembly for fuel cells, and fuel cell

    WO2023277148A1